4D printing of polyamide 1212 based shape memory thermoplastic polyamide elastomers by selective laser sintering. (28th April 2023) - Mei, Shuxiang; Wang, Jiqiang; Li, Zhen; Ding, Bowen; Li, Siyuan; Chen, Xiaoyin; Zhao, Wei; Zhang, Yuancheng; Zhang, Xiaomeng; Cui, Zhe; Fu, Peng; Pang, Xinchang; et al.
Abstract: 4D printing technology, also known as additive manufacturing technology for smart devices, offers a wide range of promising applications in aerospace, automobile, biomedical and soft robotics. However, there are only a limited number of commercialized elastomer materials for 3D printing which needs further development, especially smart elastomers. In this work, polyamide 1212 (PA1212) based thermoplastic polyamide elastomer (TPAE) was synthesized by one-pot melt polycondensation of 1, 12-dodecanedioic acid (DA), 1, 12-dodecanedioic amine (DN) and polyetheramine in a stainless steel reactor and then the TPAE powder for selective laser sintering (SLS) was obtained after freeze-crushing and sieving. Subsequently, the effects of sintering temperature, laser power, layer thickness, and scan spacing during SLS processing on the properties of the sintered parts were fully investigated. The tensile strength, elastic modulus and elongation at break of the sintered parts could reach 13.7 MPa, 124 MPa and 200 %, respectively, when the sintering temperature, laser power, layer thickness and scan spacing were set as 156 °C, 21 W, 0.10 mm and 0.10 mm, respectively. Moreover, PA1212-based TPAEs fabricated by SLS showed excellent and stable shape memory behavior. This work not only provides a designing strategy of 4D printable materials and referential SLS-processing parameters, but also broadens the application of polyamide-based elastomer materials into 4D printing fields. Graphical abstract: Unlabelled Image Highlights: PA1212-based TPAE was synthesized by one-pot melt polycondensation. A PA1212-based TPAE powder that can be used in SLS was prepared by freeze-crushing method. The SLS-processing parameters of PA1212-based TPAE were explored, and its shape memory behaviors were investigated.